Metformin modulates oxidative stress via activation of AMPK/NF-κB signaling in Trisomy 21 fibroblasts: an in vitro study - Buczyńska, Angelika; Malinowski, Piotr; Żbikowski, Arkadiusz; Krętowski, Adam Jacek; Zbucka-Krętowska, Monika (Frontiers in Molecular Biosciences, 2025)
IntroductionOxidative stress and impaired antioxidant defenses are key contributors to cellular dysfunction in Trisomy 21 (T21), highlighting the need for targeted therapeutic strategies. This study explores the modulatory effects of metformin on oxidative stress and antioxidant capacity in T21.MethodsAn in vitro model was employed using human fibroblast cells with T21 (CCL-54 – Detroit 532 and Detroit 539 – CCL-84; ATCC) alongside normal fibroblasts as a control group (PCS-201-012; ATCC). These cells were treated with varying doses of metformin (10 μM, 30 μM, and 50 μM) for 48 h to assess its pleiotropic protective effects and their impact on oxidative-metabolic cellular profiles.ResultsOur results demonstrate that metformin treatment significantly reduced total oxidative capacity (TOC) and levels of oxidative DNA/RNA damage products in T21 cell lines (CCL-84 and CCL-54). Additionally, metformin markedly increased total antioxidant capacity (TAC) in these fibroblasts. Furthermore, metformin influenced key signaling pathways, as evidenced by increased levels of nuclear factor kappa B (NF-κB) and enhanced activity of protein kinase AMP-activated alpha 1 (PRKAA1) and AMP-activated protein kinase (AMPK) in T21 cell lines.ConclusionsThese findings highlight metformin’s significant role in modulating oxidative stress and inflammation- related mechanisms in T21. Given the growing interest in managing oxidative stress during pregnancies affected by T21, this study presents potential clinical implications for therapeutic intervention.